Solve for x 4(x-3)-12=0

Math
4(x-3)-12=0
Simplify 4(x-3)-12.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
4x+4⋅-3-12=0
Multiply 4 by -3.
4x-12-12=0
4x-12-12=0
Subtract 12 from -12.
4x-24=0
4x-24=0
Add 24 to both sides of the equation.
4x=24
Divide each term by 4 and simplify.
Tap for more steps…
Divide each term in 4x=24 by 4.
4×4=244
Cancel the common factor of 4.
Tap for more steps…
Cancel the common factor.
4×4=244
Divide x by 1.
x=244
x=244
Divide 24 by 4.
x=6
x=6
Solve for x 4(x-3)-12=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top